Sep diagnosing neurophaty of the lateral cutaneous branch of the iliohypogastric nerve: case report Neuropatia do ramo cutâneo lateral do nervo ílio-hipogástrico diagnosticada por PES: relato de caso - Rafael José Soares Dias; Lancaster de Souza; Wanderley Freitas de Morais; Armando Pereira Carneiro (Arquivos de Neuro-Psiquiatria)
The article pertains to the uncommon clinical case of a patient with a proximal neuropathy of the lower extremity. It outlines the electrophysiological evaluation and reviews the medical literature. The electrophysiologic test that most accurately revealed the neuropathy was the segmental somatosensory evoked potential (SEP) of the lateral cutaneous branch of the iliohypogastric nerve. It showed well-defined and replicable cortical waveforms following the excitation of the lateral cutaneous branch of the iliohypogastric nerve in the asymptomatic lower extremity, but failed to present somatosensory evoked potentials arising from the excitation of the contralateral nerve in the symptomatic lower extremity. We did not find any previous reports diagnosing that particular pathology by the use of segmental SEP. In conclusion, it is important to remember that the accurate diagnosis of patients complaining of pain and dysesthesia in the proximal part of the lower extremities can possibly be achieved through the use of electrophysiologic tests such as the segmental SEP. O presente artigo relata caso clínico incomum de neuropatia proximal de membro inferior, demonstra eletrofisiologicamente o comprometimento neural e revisa a literatura médica sobre o assunto. O teste neurofisiológico que demonstrou a patologia foi o potencial evocado somato-sensitivo (PES) segmentar do ramo cutâneo lateral do nervo ílio-hipogástrico. Ele revelou potenciais corticais bem definidos e replicáveis à estimulação do membro inferior assintomático, mas falhou em produzir respostas corticais do membro inferior sintomático. Na revisão da literatura não foi encontrado nenhum relato anterior de diagnóstico dessa patologia por PES segmentar. Conclui-se que é importante ter em mente ao avaliar pacientes com queixas de dor e disestesia na base dos membros inferiores que o acometimento de pequenos ramos cutâneos, como o cutâneo lateral do ílio-hipogástrico, pode ter confirmação eletrofisiológica da patologia por testes neurofisiológicos como o potencial evocado somato-sensitivo segmentar.